pH-Triggered Hydrogel Nanoparticles for Efficient Anticancer Drug Delivery and Bioimaging Applications - Keristina Wagdi K. Amin; Ágota Deák; Miklós Csanády; Nikoletta Szemerédi; Diána Szabó; Árpád Turcsányi; Ditta Ungor; Gabriella Spengler; László Rovó; László Janovák (MDPI AG, 2024)
In this work, we developed multifunctional hydrogel nanoparticles (NPs) that can encapsulate anticancer drugs and imaging contrast agents as well. Mitomycin C (MMC) and rhodamine B (RB) were selected as models for anticancer drugs and imaging contrasting agents, respectively. Both MMC and RB were linked to the succinated polyvinyl alcohol polymer (PVA-SA). The selected labeled hydrogel NPs ((0.5% RB)-PVA-SA NPs and (1.5% RB)-PVA-SA NPs) improved the RB quantum yield from 29.8% to a minimum of 42.7%. Moreover, they showed higher emission stability compared to free RB when they were repeatedly excited at 554 nm for 2 h. Furthermore, the dye polymeric interactions significantly increased the RB fluorescence lifetime by approximately twofold. All these optical properties pave the way for our labeled hydrogel NPs to be used in imaging-guided therapy. For the labeled MMC-loaded NPs, the MMC-binding efficiency was found to be exceedingly high in all synthesized samples: a minimum of 92% was achieved. In addition, the obtained pH-dependent drug release profiles as well as the cytotoxicity evaluation demonstrated the high potential of releasing MMC under acidic cancerous conditions. Moreover, the in vitro cellular uptake experiment confirmed the accumulation of MMC NPs throughout the cytoplasm.